665.6: 665.6/7: 662.6/.9 TECHNICAL AND ECONOMIC ASPECTS OF PROCESSING PYROLYSIS DISTILLATE INTO MOTOR FUEL - Xudayberdiyev, Abdukarim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The main results of the study on the development of an effective technology for processing pyrolysis distillate into motor fuel, based on the catalytic process of hydrotreating raw materials and hydrogenation of intermediate technological products under relatively mild conditions, are presented. The main stages of the new technology are heating of raw materials and hydrogenated product in furnaces, two-stage catalytic processing of distillate and hydrogenated product, heating of raw materials and cooling of reaction products and separation of the gas product mixture with the release of hydrogen-containing gas.